QUALITY OF SERVICES IN TOURISM INDUSTRY AS A MODEL OF TOURISM DESTINATION MANAGEMENT - Vujko, Aleksandra; Vujnić, Jovana; Gajić, Tamara; Petrović, Marko (International Journal of Economic Practice and Policy, 2016)
The starting hypothesis in this work is the claim that the quality of services is the key to retaining existing and attracting new tourists. The goal is to show the level of consumers’ satisfaction with the quality of services in tourism and hospitality in the municipality of Bečej and point out to any possibility of increasing the quality of services provided. In this study, we used the techniques of survey research. Respondents were passers and employees in the tourism sector in the municipality of Bečej and they were asked to evaluate quality of services in tourism and hospitality and commitment of employees in tourism and catering facilities in order to better meet the needs and requirements of visitors. Based on the analysis of the dependent and independent variables, it was concluded that the quality of the tourist services in the region is not satisfactory, but that the preconditions for its improvement exists if efforts and funds are invested for this purpose. The results may be significant for providers of hotel services and contribute to the advancement of business by adapting the tourist offer and the product to the needs of guests.